COVID-19 and Diabetes Mellitus at RSU South Tangerang-Indonesia: Clinical Profile and Treatment Strategies: COVID-19 dan Diabetes Mellitus di RSU Tangerang Selatan-Indonesia: Profil Klinis dan strategi pengobatan - Hasanah, Nur; Ismaya, Nurwulan Adi; Tulandi, Silvester Maximus; Permatasari, Putri Indah; Wafa, Wafa; Hakim, Amelia Nurul (Universitas Tadulako, 2023)
Background: Diabetes Mellitus is one of the risk factors for COVID-19. This causes the morbidity and severity of COVID-19 patients to be higher in patients with diabetes. Objectivity: This study aimed to determine the effectiveness of treatment therapy for COVID-19 patients with comorbid diabetes at the South Tangerang City General Hospital. Material and methods: This study used a descriptive design with a quantitative approach and retrospective data collection. Sampling was done by Total Sampling with a total sample of 127 patients from 234 patients. Result: The characteristics of COVID-19 patients with comorbid diabetes were dominated by the male gender (55.1%), with an age range of 46-55 years (38.6%), high school education (43.3%), and have a private employee type of work (55.1%). The symptoms of COVID-19 patients with comorbid diabetes were cough (89.8%), with a length of stay for patients 7–14 days (72.4%).Treatment for COVID-19 with comorbid diabetes was antibiotics azithromycin (26.0%), antiviral remdesivir (62.2%), methylprednisolone (73.2%), acetylcysteine (85.0%), vitamin C (89.8%), and the antidiabetic group that is often used is insulin novorapid (41.7%). Conclusion: The results of laboratory examinations showed that COVID-19 treatment therapy is effective in reducing the amount of virus in the blood, which is indicated by an increase in the PCR value (p-value <0.001), lowering blood sugar levels (which is characterized by a decrease in blood sugar levels when (p-value <0.001) ), and reduce hypercoagulation which is characterized by a reduction in the value of D-dimer (p-value < 0.005).